The Modern Harpsichord. Twentieth-Century Instruments and Their Makers - Zuckermann, Wolfgang Joachim 1922-2018 (New York October House, 1969)
Wolfgang Joachim Zuckermann was born in Berlin, Germany on October 11, 1922. His family fled Nazi Germany in 1938 and settled in Manhattan, New York. During World War II, he fought with the 10th Armored Division in France and Germany. He graduated from Queens College, where he studied English and psychology. He worked for a while as a child psychologist but decided to leave the field and study piano mechanics at a trade school. He worked as a as a piano mechanic and tuner in Manhattan in the 1950s. He was also a self-taught harpsichord builder, who finished his first harpsichord in 1955. He created a low-cost do-it-yourself harpsichord kit, widely referred to as the Z-Box. He sold his company in the late 1960s. His book, The Modern Harpsichord, was published in 1969. He later wrote papers for EcoPlan International about environmental and public policy issues. He also wrote a book entitled End of the Road and collaborated with the illustrator Roger Tweedt on a book entitled Family Mouse Behind the Wheel. He died on October 31, 2018 at the age of 96.
Keywords: 20th Century (1901-2000); Harpsichord; Organology; Keyboard instrument